Innovative Methods and Technologies to Increase the Efficiency of the Energy System - Aliyev, Tural (ADA University, 2023)
The fundamental mission of the energy system is to consistently provide the required electricity to all segments of the network, while keeping to accepted economic and quality norms. Transmission lines play a crucial role in facilitating the transportation of electrical power from generation stations to end consumers. The maintenance of transmission lines and generation plants holds significant importance in ensuring power system reliability, minimizing operational costs, and prolonging the lifespan of equipment. In addition, the operation of the system with all available equipment ensures that the system is maintained at the highest degree of security.Power plants are responsible for the generation of electricity, which is subsequently transmitted and distributed to clients via power lines. High-voltage transmission lines, characterized by their suspension between towering metallic structures, serve the purpose of efficiently transporting power across extensive distances in order to cater to the demands of consumers. The utilization of higher voltage electricity proves to be more efficient and costeffective for transmitting electricity across vast distances. The utilization of lower voltage power in residential and commercial settings is associated with enhanced safety. Transformers located at substations play a crucial role in the adjustment of voltages during the various stages of electricity transmission. These transformers are responsible for either increasing (step up) or decreasing (step down) voltages to accommodate the diverse requirements encountered during the journey from power plants through long-distance transmission lines to distribution lines, which deliver electricity to residential and commercial establishments. This thesis introduces an approach for developing optimal strategies to enhance the efficiency of power systems. The topic incorporates network and operational restrictions regarding energy systems that experience seasonal variations in weather conditions, load demands, and generating patterns. Advanced materials and sophisticated procedures are employed to model and address the issue of efficacy. Moreover, an innovative strategy has been developed as well as implemented to address the significant issue of reducing the excessive time constraints associated with the current methodology
Keywords: Power transmission--Efficiency; Electric power transmission--Maintenance; Power plants--Operation; Electric power distribution--Design and construction; Electrical engineering--Transmission systems; Azerbaijan--Electric power systems; IT and Engineering